2023
DOI: 10.3390/nu15112490
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate and Nitrite Metabolism in Aging Rats: A Comparative Study

Abstract: Nitric oxide (NO) (co)regulates many physiological processes in the body. Its short-lived free radicals force synthesis in situ and on-demand, without storage possibility. Local oxygen availability determines the origin of NO—either by synthesis by nitric oxide synthases (NOS) or by the reduction of nitrate to nitrite to NO by nitrate/nitrite reductases. The existence of nitrate reservoirs, mainly in skeletal muscle, assures the local and systemic availability of NO. Aging is accompanied by changes in metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…This ability may underlie the extensively regulated blood flow in the brain, ensuring a constant supply of oxygen and nutrients. Consistent with this suggestion, previous studies [ 33 , 34 ] suggested that nitrite present in cerebral circulation serves as a source of NO, capable of compensating for compromised NOS function.…”
Section: Discussionsupporting
confidence: 69%
“…This ability may underlie the extensively regulated blood flow in the brain, ensuring a constant supply of oxygen and nutrients. Consistent with this suggestion, previous studies [ 33 , 34 ] suggested that nitrite present in cerebral circulation serves as a source of NO, capable of compensating for compromised NOS function.…”
Section: Discussionsupporting
confidence: 69%
“…nNOS−/− mice treated with high nitrate showed a trend to increase XOR protein ( p = 0.0583, unpaired t -test), while nNOS−/− mice treated with low nitrate revealed a trend to increase sialin protein ( p = 0.0594, unpaired t -test). Since skeletal muscle protein expression of sialin and XOR is highly variable between individuals, as shown in our previous study in rats and humans ( Wylie et al, 2019 ; Piknova et al, 2023 ), a significant difference in protein expression in nitrate treatments could not be notably observed. Additionally, limitations of antibody suitability and availability for Western blotting result in changes more readily detectable by mRNA expression.…”
Section: Discussionmentioning
confidence: 56%
“…Nitrate is abundant in vegetables (such as beetroot, spinach, and lettuce) and has been used as nutritional supplementation in healthy and diseased humans ( Lidder and Webb, 2013 ; Ranchal-Sanchez et al, 2020 ; Babateen et al, 2021 ; Esen et al, 2022 ). We previously demonstrated in rats and humans that nitrate supplementation increases tissue nitrate/nitrite levels, that skeletal muscle contains a nitrate transporter (sialin) and nitrate/nitrite reductase [xanthine oxidoreductase (XOR)], and that skeletal muscle nitrate acts as a regulator to maintain a systemic NO homeostasis ( Piknova et al, 2016a ; Gilliard et al, 2018 ; Wylie et al, 2019 ; Piknova et al, 2022b ; Kadach et al, 2022 ; Piknova et al, 2023 ). In a recent study, in rats administered with 15 N-labeled nitrate, we found that nitrate treatment directly increases 15 N-labeled nitrate and nitrite accumulation in skeletal muscle and upregulates skeletal muscle gene expression of nitrate transporters [ sialin and chloride channel 1 ( CLC1 )] and XOR ( Park et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that various reductase can reduce the nitrite ion to NO, increasing NO bioavailability in the body. Thus, nitrite is considered as a NO metabolite [6,7].…”
Section: Introductionmentioning
confidence: 99%